Compulsory Licensing for Pharmaceutical Access in East Africa: The Challenge of Kenya's Failure to Adopt Article 31bis of the TRIPS Agreement - Miriti, Vicky (Strathmore Law Review, 2024)
Sub-Saharan Africa, including East Africa, grapples with profound public health challenges exacerbated by limited access to pharmaceuticals. The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement), enacted in 1995, introduced patent rights for pharmaceuticals, restricting generic production. Even so, Article 31 of the TRIPS Agreement permits compulsory licensing to facilitate cheaper generic versions, but this is underutilised by smaller economies like those in the East African Community (EAC) due to economic constraints. To help address this challenge, Article 31bis allows countries in a Regional Trade Agreement (RTA) to pool demand and import medicines collectively, thus boosting economies of scale. It also permits local manufacturing and re-export of pharmaceuticals within the RTA. The EAC qualifies for this mechanism, but many of its members lack the implementation legislation required to use the system. This paper focuses on the implications of Kenya’s lack of such implementing legislation to medicine accessibility in the EAC. This is because it is well positioned, given its growing pharmaceutical sector, to potentially become a regional hub for medicine production and to attract foreign supplies. Although creating such legislation will not solve all the challenges around the usage of compulsory licenses, its creation is important to ensure the system is available to the EAC in its aspiration to increase the accessibility of medicines.